High Sensitivity photoelectron yield spectroscopy with computer-calculated electron optics - Ristein, Jürgen; Ley, Lothar; et al. (Review of Scientific Instruments, 1993)
An improved spectrometer design for photoelectron yield spectroscopy is described. Basis of the new spectrometer is a computer-designed electron optics that images the emission spot into the electron multiplier and thereby improves the sensitivity for electrons emitted from the sample. The collection efficiency was experimentally determined to 98.3%. A background of stray electrons which limits the ultimate sensitivity of the method could be substantially reduced by minimizing multiple beam reflections and by coating critical surfaces with a high work function material such as platinum. As a result, photoyield spectra of Au with a dynamical range of ten orders of magnitude are routinely obtained.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.highse